Hubungan Status Gizi Terhadap Kejadian Dislipidemia pada Mahasiswa Program Pendidikan Dokter Spesialis Ilmu Penyakit Dalam RSUP Prof. dr. I.G.N.G. Ngoerah - I Dewa Gede Agung Suta Ariwangsa; I Made Pande Dwipayana (PT Dexa Medica, 2026)
Background: Nutritional status plays an important role in determining individual’s health. Obesity is closely associatedwith dyslipidemia, mainly through insulin resistance mechanisms and proinflammatory adipokines, which contribute tothe development of metabolic syndrome. However, recent evidence suggests that obesity‑related dyslipidemia does notfollow a single, uniform pathophysiological pattern; instead, its characteristics may vary across individuals. This studyaimed to examine the relationship between nutritional status and dyslipidemia among residents of the Internal Medicine Specialist Program at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar. Methods: This cross‑sectional study was conducted in August 2023 at RSUP Prof. dr. I.G.N.G. Ngoerah, Denpasar. The study subjects were residents of the Internal Medicine Specialist Program. Data were collected through measurements of body mass index (BMI) as an indicator of nutritional status and lipid profile examination as an indicator of dyslipidemia. The association between variables was analyzed using the Chi‑Square test, with statistical significance set at p<0.05. Results: A total of 115 subjects were enrolled in the study, with 60% men and 40% women and a mean age of 31.25 ± 3.82 years. Of these, 74 subjects (64,3%) were classified as obese, and 57 subjects had dyslipidemia. Forty‑six (46) subjects had presented with obesity and dyslipidemia, while 11subjects had dyslipidemia in the absence of obesity. Meanwhile, 30 subjects had neither obesity nor dyslipidemia, and 28 participants were obese without dyslipidemia. The Chi‑Square test showed a significant association between nutritional status and dyslipidemia (p<0,001). Conclusion: This study demonstrates a significant relationship between nutritional status and dyslipidemia. Further research is needed to explore specific factors that contribute to obesity and dyslipidemia among residents in specialist medical training programs.Keywords: nutritional status, obesity, dyslipidemia, resident physicians, PPDS